2015
DOI: 10.1055/s-0035-1549911
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Clinical Outcome of CYP21A2 Gene Mutations in Patients with Nonfunctional Adrenal Incidentalomas

Abstract: Adrenal tumors, discovered incidentally in approximately 4.5% of imaging procedures, are known as adrenal incidentalomas. Nonclassic congenital adrenal hyperplasia, mild form of 21-hydroxylase deficiency, may lead to the development of adrenocortical tumors. The aim of the study was to evaluate prevalence of the most common nonclassic mutations of CYP21A2 gene in patients with adrenal incidentalomas and investigate possible relationship with clinical outcome. One hundred adult patients with such lesions were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…This led to studies of enzyme mutation that varied in their findings, two studies found no mutation in small numbers of patients, 25,26 but in a study of 50 patients, the prevalence was 16%-21% 27 and in another study of 100 adults was 8%,. 28 In a metaanalysis of adrenal hyperplasia cases screened for Cyp21A2 mutations, 58/990 of cases (6%) were diagnosed as CAH but only 0.8% were confirmed genetically, 29 and others have shown no relation between the 17-OH Progesterone response and the mutation. 30 In two studies, patients showed an increased response in serum 17-OH Progesterone after ACTH stimulation, but following adrenalectomy, the repeat ACTH stimulation test showed much lower increase in serum 17-OH Progesterone suggesting that the increase in 17-OH Progesterone was not a generalized defect in enzyme activity but specific to the tumour.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This led to studies of enzyme mutation that varied in their findings, two studies found no mutation in small numbers of patients, 25,26 but in a study of 50 patients, the prevalence was 16%-21% 27 and in another study of 100 adults was 8%,. 28 In a metaanalysis of adrenal hyperplasia cases screened for Cyp21A2 mutations, 58/990 of cases (6%) were diagnosed as CAH but only 0.8% were confirmed genetically, 29 and others have shown no relation between the 17-OH Progesterone response and the mutation. 30 In two studies, patients showed an increased response in serum 17-OH Progesterone after ACTH stimulation, but following adrenalectomy, the repeat ACTH stimulation test showed much lower increase in serum 17-OH Progesterone suggesting that the increase in 17-OH Progesterone was not a generalized defect in enzyme activity but specific to the tumour.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies showed an exaggerated response in serum 17‐hydroxyprogesterone to ACTH in adrenal incidentalomas 9,22‐24 suggesting a partial deficiency in the activity of the 21‐hydroxylase enzyme. This led to studies of enzyme mutation that varied in their findings, two studies found no mutation in small numbers of patients, 25,26 but in a study of 50 patients, the prevalence was 16%–21% 27 and in another study of 100 adults was 8%, 28 . In a meta‐analysis of adrenal hyperplasia cases screened for Cyp21A2 mutations, 58/990 of cases (6%) were diagnosed as CAH but only 0.8% were confirmed genetically, 29 …”
Section: Discussionmentioning
confidence: 99%
“…Our patient is obese, has bilateral adrenal nodules, and has hypertension controlled with amlodipine and spironolactone. She has no features of virilization and has not been analyzed for CYP21A2 gene mutations or genome-wide mosaic paternal uniparental disomy [14,15]. Primary aldosteronism seems unlikely and we did not measure deoxycorticosterone in our patient [16].…”
Section: Dear Editorsmentioning
confidence: 98%
“…Hormonal panels were focused on CAH diagnosis depending on the specific enzyme defect. Eleven studies provided data regarding ACTH values for 11/22 subjects [73,77,[79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95][96][97]; the hormone was increased in 8/11 cases [77,[79][80][81]84,86,87,89], out of which 4/8 had tumours >10 cm [81,84,86,87], and 4/8 had tumours of 5-10 cm [77,79,80,89]; ranges varied between 37.5 pg/mL (which is a normal value; overall, N = 3 individuals had normal ACTH) [83] and 2000 pg/mL [77] (average of 342.9 pg/mL; median of 166 pg/mL). Tumour size-ACTH analyses showed in cases with masses larger than 10 cm, respectively, between 5 and 10 cm, a mean ACTH of 128 pg/mL and 753.8 pg/mL, respectively.…”
Section: Adrenal Tumours In Patients Diagnosed With Cah Without a Gen...mentioning
confidence: 99%
“…Apart from the mentioned case reports/series, nine studies [90][91][92][93][94][95][96][97][98] addressed the issue of CAH and adrenal tumours from different perspectives, such as CAH prevalence among the individuals diagnosed with adrenal tumours/incidentalomas [90][91][92] or long-term outcomes in relationship with disease control and adrenal morphology, particularly, the identification of distinct adrenal tumours [93][94][95][96][97][98].…”
Section: Prevalence Studies On Cah and Adrenal Tumoursmentioning
confidence: 99%